2018
DOI: 10.1111/bju.14461
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of nivolumab for metastatic renal cell carcinoma: real‐world results from an expanded access programme

Abstract: The safety and efficacy observed were consistent with those reported in the pivotal Checkmate 025 trial. Results in patients with non-clear-cell mRCC who were elderly, pretreated with everolimus, and had bone and/or brain metastases encourage the use of nivolumab in these categories of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 20 publications
7
51
0
1
Order By: Relevance
“…We previously conducted an analysis of the Italian RCC EAP, which showed that efficacy and safety of nivolumab for the treatment of metastatic RCC were comparable to phase III results; OS, PFS, and ORR in our cohort were similar to the observations in the CheckMate 025 studies (1,20).…”
Section: Discussionsupporting
confidence: 78%
“…We previously conducted an analysis of the Italian RCC EAP, which showed that efficacy and safety of nivolumab for the treatment of metastatic RCC were comparable to phase III results; OS, PFS, and ORR in our cohort were similar to the observations in the CheckMate 025 studies (1,20).…”
Section: Discussionsupporting
confidence: 78%
“…In this study, results suggested that AE profiles differ between nivolumab and axitinib. The AE status of the nivolumab-administered group in our study is similar to that of the Check Mate 025 study and the study by De Giorgi et al (1,12). The absence of subjective symptoms, such as nausea, maintains the quality of life (QOL) of the nivolumab-administered patients.…”
Section: Nivolumab N=9supporting
confidence: 86%
“…A study by Lalani et al on 142 patients treated with ICIs in any line confirmed that patients with a higher baseline NLR had a worse prognosis and reported that NLR decrease ≥25% during ICI treatment was significantly associated with improved outcomes (both PFS and OS) [162].…”
Section: Inflammation As Predictive Factormentioning
confidence: 93%